A phosphate binder and preparation method thereof
By adding sodium copper ethylenediaminetetraacetate modifier to the phosphate binder, a macromolecular structure with complex structure is formed, which solves the problems of unstable performance, poor hygroscopic resistance and poor fluidity of the phosphate binder, and achieves high bond strength, low viscosity and good hygroscopic resistance.
Patent Information
- Application Number
- CN202111623638.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-28
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-12-28
AI Technical Summary
In actual production, phosphate binders have problems such as unstable performance, poor hygroscopic resistance, large viscosity and poor fluidity of molded sand, which are difficult to meet the same strength requirements as traditional organic resin binders.
Sodium copper ethylenediaminetetraacetate is used as a modifier to form chelation or bonding with metal ions such as acid ions and aluminum ions to form a complex macromolecular structure, improve the bonding strength and moisture resistance of phosphate binders, and reduce their viscosity.
It significantly improves the bonding strength and hygroscopic resistance of the phosphate binder, reduces the viscosity, improves the fluidity of the molded sand, and meets the actual production strength and fluidity requirements.
Smart Images

Figure BDA0003439153580000021 
Figure BDA0003439153580000022 
Figure BDA0003439153580000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of casting technology, and in particular to a phosphate binder and a preparation method thereof. Background Art
[0002] At present, the widely used inorganic binders include: phosphate binders, silicate binders, and borate binders. Compared with silicate binders, phosphate binders have good water resistance, small curing shrinkage, high high temperature strength and can be cured at lower temperatures.
[0003] As a green and environmentally friendly inorganic casting binder, phosphate binder has the characteristics of good disintegration, colorlessness, and non-irritating odor, which can significantly reduce environmental pollution. However, compared with traditional organic resin binders, it has the disadvantages of unstable performance, poor moisture absorption resistance, high viscosity, and poor sand fluidity.
[0004] According to the relevant characteristics of phosphate binders, they are modified, such as the addition of some simple small molecular weight acid modifiers, which improves the performance of phosphate binders to a certain extent, but does not significantly improve the strength and fluidity of sand samples. In order to achieve the same strength requirements as traditional organic resin binders, more phosphate binders need to be added. How to modify phosphate binders, improve their strength to reduce the amount of phosphate binders added, increase their neutralization degree, reduce their viscosity, and improve the fluidity of molding sand to meet actual production needs is the main problem at present. Summary of the invention
[0005] In order to solve the above-mentioned deficiencies in the art, the present application aims to provide a phosphate binder and a preparation method thereof. The binder of the present application has the advantages of high bonding strength, good moisture resistance, low viscosity, and good fluidity of the prepared molding sand.
[0006] This application achieves one of the objectives by using the following technical solution:
[0007] A phosphate binder modified by sodium copper ethylenediaminetetraacetate is mainly prepared from the following raw materials by mass percentage:
[0008]
[0009] According to some embodiments of the present application, a phosphate binder modified by sodium copper ethylenediaminetetraacetate is prepared from raw materials including the following components in mass percentage:
[0010]
[0011] Furthermore, the industrial phosphoric acid is 85% by mass of industrial phosphoric acid.
[0012] Aluminum hydroxide powder is industrial grade white powder with a particle size of 300-350 mesh.
[0013] Silicic acid was analytically pure white amorphous powder.
[0014] Boric acid is analytically pure in the form of colorless, slightly pearly crystalline white powder with an effective content of ≥99.9%.
[0015] Light magnesium oxide is analytically pure and is a white light powder with an effective content of ≥98.5%.
[0016] Sodium copper ethylenediaminetetraacetate is a blue powder with a copper content of 15% and is analytically pure.
[0017] The water is deionized pure water.
[0018] The following technical solutions are used to achieve the second purpose of this application:
[0019] A method for preparing the above-mentioned phosphate binder comprises:
[0020] Add raw materials, industrial phosphoric acid, aluminum hydroxide powder, boric acid, silicic acid, light magnesium oxide, sodium copper ethylenediaminetetraacetate and water into the reaction kettle in sequence; react until the solution becomes transparent, and remove the bottom precipitate after discharging.
[0021] The above raw materials are added sequentially. In the first step, phosphoric acid and aluminum hydroxide are added to react to obtain the required base aluminum dihydrogen phosphate. Boric acid and silicic acid are then added to promote the dissolution of light magnesium oxide added in the next step. Finally, sodium copper ethylenediaminetetraacetate is added to ensure sufficient reaction to obtain the desired ideal product.
[0022] Furthermore, after adding the aluminum hydroxide powder, when the reaction liquid becomes transparent, water is added to continue the reaction; after adding the silicic acid, when the reaction liquid becomes transparent, water is added to continue the reaction.
[0023] Furthermore, after adding the sodium copper ethylenediaminetetraacetate, when the reaction solution becomes transparent, water is added to continue the reaction.
[0024] After adding boric acid, wait until the reaction solution becomes transparent, then add silicic acid.
[0025] The above reaction temperature is 180-200°C.
[0026] Specifically, a method for preparing a phosphate binder modified by sodium copper ethylenediaminetetraacetate comprises the following steps:
[0027] (1) Add industrial phosphoric acid into a reaction kettle and heat to 180-200°C while stirring;
[0028] (2) adding aluminum hydroxide powder in small amounts to the reaction kettle of step (1) above several times, and continuing to stir until the reaction solution becomes transparent;
[0029] (3) adding one quarter of the total amount of water to the reaction kettle in step (2), and heating and stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0030] (4) Adding boric acid to the reaction kettle of step (3) above, and continuing to heat and stir until the reaction solution becomes transparent;
[0031] (5) adding silicic acid to the reaction kettle of step (4) above, and continuing heating and stirring until the reaction solution becomes transparent;
[0032] (6) adding one quarter of the total amount of water to the reaction kettle in step (5), and heating and stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0033] (7) Adding light magnesium oxide to the reaction kettle of step (6) above, and continuing to heat and stir until the reaction solution becomes transparent;
[0034] (8) adding one quarter of the total amount of water to the reaction kettle of step (7), and heating and stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0035] (9) Adding sodium copper ethylenediaminetetraacetate to the reaction kettle of step (8) above, and continuing heating and stirring until the reaction solution becomes transparent;
[0036] (10) Add the remaining water of the total water volume to the reaction kettle of the above step (9), continue heating and stirring until the reaction solution is transparent and clear, and remove the bottom precipitate after discharging to obtain the phosphate binder modified by sodium copper ethylenediaminetetraacetate.
[0037] The present application provides a phosphate binder modified by sodium copper ethylenediaminetetraacetate, wherein sodium copper ethylenediaminetetraacetate is used as a modifier. Sodium copper ethylenediaminetetraacetate is a stable water-soluble metal chelate. The sodium copper ethylenediaminetetraacetate contains a high amount of effective ingredients, and the formed chelate has more stable performance. The binder prepared by sodium copper ethylenediaminetetraacetate can be stably stored for a long time without crystallization, and the viscosity is also very stable.
[0038] The phosphate binder modified by sodium copper ethylenediaminetetraacetate of the present application has low viscosity, and its viscosity range is 145.8-148.3 mPa.s. The strength of the sand sample prepared by using the phosphate binder modified by sodium copper ethylenediaminetetraacetate of the present application is improved, and the fluidity of the molding sand is also improved.
[0039] The molding sand prepared with the sodium copper ethylenediaminetetraacetic acid modified binder of the present application has better fluidity, reduces the filling resistance, is beneficial to the filling of the sand, and is thus beneficial to improving the strength of the sand mold, thereby offsetting the effect of the increase in neutralization degree to a certain extent. Since the binder of the present application has a high degree of neutralization, its anti-hygroscopicity is significantly improved.
[0040] The phosphate binder modified by sodium copper ethylenediaminetetraacetate of the present application adopts sodium copper ethylenediaminetetraacetate as a modifier, which can be connected to the phosphate network structure with a small addition amount, thereby increasing the flexibility of the network structure and the length of the chain segments, thereby significantly reducing the viscosity of the binder, improving the fluidity of the molding sand, and improving the strength of the sand sample prepared by the molding sand.
[0041] The preparation method of the sodium copper ethylenediaminetetraacetate modified phosphate binder of the present application can maximize the participation of the added raw materials in the reaction, produce less residue, and reduce water loss to ensure that the binder has a lower viscosity. DETAILED DESCRIPTION
[0042] As mentioned above, the current phosphate binder has the disadvantages of unstable performance, poor moisture absorption resistance, high viscosity, poor sand fluidity, etc. In view of the above problems, the present application provides a phosphate binder modified by sodium copper ethylenediaminetetraacetate and a preparation method thereof.
[0043] The technical solution of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0044] It is particularly important to point out that similar substitutions and modifications made to the present application are obvious to those skilled in the art, and they are all deemed to be included in the present application. Relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present application to implement and apply the technology of the present application. Obviously, the described embodiments are only some embodiments of the present application, not all embodiments.
[0045] If no specific conditions are specified in this application, the preparation shall be carried out under conventional conditions or the conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, for which the manufacturers are not specified, are all conventional products that can be obtained commercially.
[0046] According to the technical concept of the present application, a phosphate binder and a preparation method thereof are provided.
[0047] The application is described in detail below.
[0048] A phosphate binder modified by sodium copper ethylenediaminetetraacetate is prepared from the following raw materials by mass percentage:
[0049]
[0050] The copper content of the sodium copper ethylenediaminetetraacetate is 15%.
[0051] The mass percentage of the industrial phosphoric acid is 85%.
[0052] The silicic acid, boric acid and light magnesium oxide are all analytically pure.
[0053] The phosphate binder modified by sodium copper ethylenediaminetetraacetate of the present application is based on the following principle: sodium copper ethylenediaminetetraacetate is an organic substance, which is characterized by being easily soluble in water and soluble in acid. According to tests, when a very small amount of the phosphate binder modified by sodium copper ethylenediaminetetraacetate is added, the strength of the prepared sand sample is improved, the fluidity of the molding sand is improved, and the viscosity of the binder is significantly reduced.
[0054] When 2.5wt% of phosphate binder modified by sodium copper ethylenediaminetetraacetate and two auxiliary materials, 0.3% KH-550 and 0.3% 12.5% oxalic acid aqueous solution, were added, the instant tensile strength of the sand sample could reach a maximum of 1.709MPa, the 6h tensile strength could reach 1.811MPa, the instant flexural strength of the sand sample could reach a maximum of 4.72MPa, the 24h flexural strength could reach 4.247MPa, and the viscosity dropped from 159.2mPa·s to 145.8mPa·s.
[0055] The reason for the above effect is that sodium copper ethylenediaminetetraacetate forms a complex macromolecular structure with metal ions such as acid radical ions and aluminum ions through chelation or bonding. The above macromolecule plays a key role in the stability and water retention of the modified binder, and in an acidic environment it is connected to the phosphoric acid network structure, increasing the flexibility of the network structure and the length of the main chain, thereby enhancing its wrapping effect and bonding performance, thereby improving the performance of the above modified binder. In addition, the addition of silicate, boric acid, and light magnesium oxide further enhances the high temperature resistance of the phosphate binder, and affects the strength and moisture absorption resistance of the sand mold.
[0056] The present application is described in detail below with reference to specific embodiments.
[0057] Example 1
[0058] The phosphate binder modified by sodium copper ethylenediaminetetraacetate in the present application has the following raw material ratio:
[0059] 338g 85% industrial phosphoric acid, 82g 320 mesh aluminum hydroxide powder, 12g boric acid, 4g silicic acid, 8g light magnesium oxide, 4g sodium copper ethylenediaminetetraacetate, and 200g purified water.
[0060] The preparation method is as follows:
[0061] (1) Add phosphoric acid into a reaction kettle and heat to 180-200° C. while stirring;
[0062] (2) adding aluminum hydroxide powder into the reaction kettle in small amounts and repeatedly, and continuing to stir until the reaction solution becomes transparent;
[0063] (3) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0064] (4) Add boric acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0065] (5) Add silicic acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0066] (6) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0067] (7) Add magnesium oxide powder and continue heating and stirring until the reaction solution becomes transparent;
[0068] (8) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0069] (9) adding sodium copper ethylenediaminetetraacetate and continuing heating and stirring until the reaction solution becomes transparent;
[0070] (10) Add 50 g of water, continue heating and stirring until the reaction solution is transparent and clear, remove the bottom precipitate after discharging, and obtain the phosphate binder modified by sodium copper ethylenediaminetetraacetate.
[0071] Example 2
[0072] The phosphate binder modified by sodium copper ethylenediaminetetraacetate in the present application has the following raw material ratio:
[0073] 338g 85% industrial phosphoric acid, 82g 300 mesh aluminum hydroxide powder, 12g boric acid, 4g silicic acid, 8g light magnesium oxide, 8g sodium copper ethylenediaminetetraacetate, and 200g purified water.
[0074] The preparation method is the same as Example 1.
[0075] Example 3
[0076] The phosphate binder modified by sodium copper ethylenediaminetetraacetate in the present application has the following raw material ratio:
[0077] 338g 85% industrial phosphoric acid, 82g 350 mesh aluminum hydroxide powder, 12g boric acid, 4g silicic acid, 8g light magnesium oxide, 12g sodium copper ethylenediaminetetraacetate, and 200g purified water.
[0078] The preparation method is the same as Example 1.
[0079] Comparative Example 1
[0080] The phosphate binder modified by sodium copper ethylenediaminetetraacetate is not used, and the raw material ratio is as follows:
[0081] 338g 85% industrial phosphoric acid, 82g 320 mesh aluminum hydroxide powder, 12g boric acid, 4g silicic acid, 8g light magnesium oxide, and 200g pure water.
[0082] The preparation method is as follows:
[0083] (1) Add phosphoric acid into a reaction kettle and heat to 180-200° C. while stirring;
[0084] (2) adding aluminum hydroxide powder into the reaction kettle in small amounts and repeatedly, and continuing to stir until the reaction solution becomes transparent;
[0085] (3) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0086] (4) Add boric acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0087] (5) Add silicic acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0088] (6) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0089] (7) Add magnesium oxide powder and continue heating and stirring until the reaction solution becomes transparent;
[0090] (8) Add 100 g of water, heat and stir until the temperature of the reaction solution returns to the temperature before adding water, thereby obtaining a phosphate binder that is not modified with sodium copper ethylenediaminetetraacetate.
[0091] Comparative Example 2
[0092] The phosphate binder modified by sodium copper ethylenediaminetetraacetate is not used, and the raw material ratio is as follows:
[0093] 338g of 85% industrial phosphoric acid, 82g of 320-mesh aluminum hydroxide powder, 12g of boric acid, 4g of silicic acid, 8g of light magnesium oxide, 12g of disodium ethylenediaminetetraacetate (EDTA-2Na), and 200g of purified water.
[0094] The preparation method is as follows:
[0095] (1) Add phosphoric acid into a reaction kettle and heat to 180-200° C. while stirring;
[0096] (2) adding aluminum hydroxide powder into the reaction kettle in small amounts and repeatedly, and continuing to stir until the reaction solution becomes transparent;
[0097] (3) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0098] (4) Add boric acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0099] (5) Add silicic acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0100] (6) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0101] (7) Add magnesium oxide powder and continue heating and stirring until the reaction solution becomes transparent;
[0102] (8) Add 100 g of water, heat and stir until the temperature of the reaction solution returns to the temperature before adding water;
[0103] (9) Add EDTA-2Na powder, continue heating and stirring until the reaction solution is transparent and clear, thereby obtaining a phosphate binder that is not modified with sodium copper ethylenediaminetetraacetate.
[0104] Comparative Example 3
[0105] The phosphate binder modified by sodium copper ethylenediaminetetraacetate is not used, and the raw material ratio is as follows:
[0106] 338g of 85% industrial phosphoric acid, 82g of 320-mesh aluminum hydroxide powder, 12g of boric acid, 4g of silicic acid, 8g of light magnesium oxide, 8g of disodium ethylenediaminetetraacetate (EDTA-2Na), and 200g of purified water.
[0107] The preparation method is as follows:
[0108] (1) Add phosphoric acid into a reaction kettle and heat to 180-200° C. while stirring;
[0109] (2) adding aluminum hydroxide powder into the reaction kettle in small amounts and repeatedly, and continuing to stir until the reaction solution becomes transparent;
[0110] (3) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0111] (4) Add boric acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0112] (5) Add silicic acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0113] (6) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0114] (7) Add magnesium oxide powder and continue heating and stirring until the reaction solution becomes transparent;
[0115] (8) Add 100 g of water, heat and stir until the temperature of the reaction solution returns to the temperature before adding water;
[0116] (9) Add EDTA-2Na powder, continue heating and stirring until the reaction solution is transparent and clear, thereby obtaining a phosphate binder that is not modified with sodium copper ethylenediaminetetraacetate.
[0117] Comparative Example 4
[0118] The phosphate binder modified by sodium copper ethylenediaminetetraacetate is not used, and the raw material ratio is as follows:
[0119] 338g of 85% industrial phosphoric acid, 82g of 320-mesh aluminum hydroxide powder, 12g of boric acid, 4g of silicic acid, 8g of light magnesium oxide, 4g of disodium ethylenediaminetetraacetate (EDTA-2Na), and 200g of purified water.
[0120] The preparation method is as follows:
[0121] (1) Add phosphoric acid into a reaction kettle and heat to 180-200° C. while stirring;
[0122] (2) adding aluminum hydroxide powder into the reaction kettle in small amounts and repeatedly, and continuing to stir until the reaction solution becomes transparent;
[0123] (3) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0124] (4) Add boric acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0125] (5) Add silicic acid powder and continue heating and stirring until the reaction solution becomes transparent;
[0126] (6) Add 50 g of water and heat with stirring until the temperature of the reaction solution returns to the temperature before adding water;
[0127] (7) Add magnesium oxide powder and continue heating and stirring until the reaction solution becomes transparent;
[0128] (8) Add 100 g of water, heat and stir until the temperature of the reaction solution returns to the temperature before adding water;
[0129] (9) Add EDTA-2Na powder, continue heating and stirring until the reaction solution is transparent and clear, thereby obtaining a phosphate binder that is not modified with sodium copper ethylenediaminetetraacetate.
[0130] Test example
[0131] The phosphate binder modified with sodium copper ethylenediaminetetraacetate prepared in Examples 1-3 and Comparative Examples 1-4 or the phosphate binder not modified with sodium copper ethylenediaminetetraacetate was used to prepare a sand mold and test its performance. The specific method is as follows:
[0132] 1. Sample preparation: Weigh 50 g of the binder of Examples 1-3 and Comparative Examples 1-4, and prepare samples according to the following methods:
[0133] Weigh 50g of phosphate binder modified by sodium copper ethylenediaminetetraacetate or phosphate binder not modified by sodium copper ethylenediaminetetraacetate, and add 6g of KH-550 and 6g of 12.5% oxalic acid aqueous solution. First add KH-550 and mix the sand for 50s, then add the binder and oxalic acid aqueous solution and mix the sand for 120s, add to 2000g of standard quartz sand, stir well, fill the stirred sand into the sand shooting mold, use a sand shooting machine to shoot the sand for 4 seconds, heat at 150°C, heat for 2 minutes when preparing tensile sand samples, and heat for 3 minutes when preparing bending sand samples.
[0134] 2. Performance test:
[0135] (1) Testing the tensile strength of sand samples: Test the immediate tensile strength of sand samples after hardening and the tensile strength after 6 hours (30%-55% RH constant humidity storage) and compare them (6 samples are tested in each group, and the average is taken after removing the highest and lowest values).
[0136] (2) Testing the flexural strength of sand samples: Testing the immediate flexural strength and 24-hour flexural strength of sand samples after hardening (30%-55% RH constant humidity storage) and comparing them (6 samples were tested in each group, and the average was taken after removing the highest and lowest values).
[0137] Table 1 Performance test results (1)
[0138]
[0139] From the results in Table 1, it can be seen that the average instant tensile strength of the sand mold prepared in Examples 1-3 ranges from 1.524 to 1.709 MPa, and the average 6h tensile strength ranges from 1.566 to 1.811 MPa; the average instant tensile strength of the sand mold prepared in Comparative Example 1 is 1.444 MPa, and the average 6h tensile strength is 1.449 MPa; the average instant tensile strength of the sand mold prepared in Comparative Examples 2-4 is 1.489 to 1.508 MPa, and the average 6h tensile strength is 1.468 to 1.514 MPa. In contrast, the 6-hour strength of Examples 1-3 is higher than that of the comparative example on average, and the increase is more obvious.
[0140] The results show that by adding a small amount of sodium copper ethylenediaminetetraacetate to the binder, the immediate hardening strength and 6-hour strength (30%-55% RH constant humidity warehouse) of the sand sample are significantly improved, the moisture absorption resistance is also improved, and the storage stability is better.
[0141] Table 2 Performance test results (2)
[0142]
[0143] From the results in Table 2 above, it can be seen that the average range of the instant bending strength of the sand mold prepared in Examples 1-3 is 4.042-4.72MPa, and the average range of the 24h bending strength is 4.016-4.247MPa; the average instant bending strength of the sand mold prepared in Comparative Example 1 is 3.604MPa, and the average 24h bending strength is 3.453MPa; the average instant bending strength of the sand mold prepared in Comparative Examples 2-4 is 3.845-3.893MPa, and the average 24h bending strength is 3.695-3.776MPa. In contrast, the 24h strength of Examples 1-3 is higher than the strength in the comparative example on average, indicating that the moisture absorption resistance of the embodiments is better than that of the comparative example.
[0144] The results show that compared with the phosphate binder without adding a small amount of sodium copper ethylenediaminetetraacetate (2.5wt%), the immediate hardening strength and 24-hour strength (30%-55%RH constant humidity storage) of the sand sample are significantly improved, the moisture absorption resistance is also improved, and the viscosity of the binder is lower and the storage stability is better.
[0145] 3. Viscosity test: The viscosity of the phosphate binders prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested using a digital viscometer, using a No. 1 rotor, a rotation speed of 12 RPM, and a temperature of 20°C.
[0146] 4. Sand fluidity: The side hole mass method is used to test the sand fluidity. The test method is as follows: weigh 185g of the sand mixture sample, add it to the standard sample tube (diameter is 12mm), put it on the hammer-type sample making machine, pull out the plug and pound it 10 times, and use the top sample column to push the sample out. Scrape the sand left in the small hole and weigh it together with the squeezed sand. The mass fraction of it in the sample is used as the fluidity index of the sand.
[0147] Table 3 Adhesive viscosity and fluidity test results
[0148]
[0149] From the results in Table 3, it can be seen that the viscosity of the adhesives prepared in Examples 1-3 ranges from 145.8 to 148.3 MPa.s; the viscosity of the adhesive prepared in Comparative Example 1 is 159.2 MPa.s; and the viscosity of the adhesives prepared in Comparative Examples 2-4 is 226.2 to 295 MPa.s.
[0150] The fluidity of the molding sand made with the binder prepared in Examples 1-3 is in the range of 1.78% to 1.86%; the fluidity of the molding sand made with the binder prepared in Comparative Example 1 is 1.56%; the fluidity of the molding sand made with the binder prepared in Comparative Examples 2-4 is 1.53 to 1.65%.
[0151] The results show that as the amount of sodium copper ethylenediaminetetraacetate added increases, the viscosity of the binder decreases, and the fluidity of the prepared molding sand improves. When the amount of sodium copper ethylenediaminetetraacetate added increases from 4g to 12g, the viscosity of the binder decreases significantly. When the amount of sodium copper ethylenediaminetetraacetate added is 8g, the fluidity of the molding sand prepared by the binder is the best.
[0152] The description of the above embodiments is only used to help understand the method and core idea of the present application. It should be noted that, for ordinary technicians in this technical field, several improvements and modifications can be made to the present application without departing from the principles of the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.
Claims
1. A phosphate binder, characterized in that: It is prepared from raw materials comprising the following components in percentage by weight:
2. The phosphate binder according to claim 1, characterized in that It is prepared from raw materials comprising the following components in percentage by weight:
3. The phosphate binder according to claim 1, characterized in that The copper content of the sodium copper ethylenediaminetetraacetate is 15% and the blue powder is analytically pure.
4. The phosphate binder according to claim 1, characterized in that The light magnesium oxide is analytically pure and is a white light powder with an effective content of ≥98.5%.
5. The phosphate binder according to claim 1, characterized in that The aluminum hydroxide powder has a particle size of 300-350 meshes.
6. A method for preparing the phosphate binder according to any one of claims 1 to 5, characterized in that: include: Add raw materials, industrial phosphoric acid, aluminum hydroxide powder, boric acid, silicic acid, light magnesium oxide, sodium copper ethylenediaminetetraacetate and water into the reaction kettle in sequence; React until the solution becomes transparent, and remove the bottom precipitate after discharging.
7. The preparation method according to claim 6, characterized in that: After adding the aluminum hydroxide powder, when the reaction liquid becomes transparent, add water to continue the reaction; After adding the silicic acid, when the reaction liquid becomes transparent, water is added to continue the reaction.
8. The preparation method according to claim 6, characterized in that: After adding the sodium copper ethylenediaminetetraacetate, wait until the reaction solution becomes transparent, then add water to continue the reaction.
9. The preparation method according to claim 6, characterized in that: After adding boric acid, wait until the reaction solution becomes transparent, then add silicic acid.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The reaction temperature is 180-200°C.
Citation Information
Patent Citations
Phosphate binding agent modified by 1-hydroxyethylidene-1,1-diphosphonic acid and preparing method of phosphate binding agent
CN110625060A
Curing agent for inorganic precoated sand and inorganic precoated sand core containing curing agent
CN112743036A